Open your eyes : deaf studies talking - Deaf Studies Think Tank (2002 : Gallaudet University); Bauman, H-Dirksen L., 1964- (Minneapolis : University of Minnesota Press, 2008)
Moving beyond proving the existence of deaf culture. Open Your Eyes shows how the culture contributes vital insights on issues of identity, language, and power and, ultimately, challenges our culture's obsession with normalcy.
Talking culture and culture talking / Tom Humphries -- Colonialism and resistance / Paddy Ladd -- The deaf convert culture and its lessons for deaf theory / Frank Bechter -- Upon the formation of a visual variety of the human race / Benjamin Bahan -- Coequality and transnational studies / Joseph J. Murray -- Sound and belonging / Hilde Haualand -- On the disconstruction of (sign) language in the western tradition / H-Dirksen L. Bauman -- Turning literacy inside out / Marlon Kuntze -- Critical pedagogy and ASL videobooks / Lawrence Fleischer -- The decline of deaf clubs in the United States / Carol Padden -- Think-between / Brenda Jo Brueggemann -- Border crossings by hearing children of deaf parents / Robert Hoffmeister -- Dysconscious audism / Genie Gertz -- The burden of racism and audism / Lindsay Dunn -- Where is deaf HERstory? / Arlene Blumenthal Kelly -- Queer as deaf / MJ Bienvenu -- Do deaf people have a disability? / Harlan Lane -- Beyond culture / Douglas C. Baynton -- Postdeafness / Lennard J. Davis.
"This book was born out of the Deaf Studies Think Tank, a three-day symposium in the summer of 2002"--Pref.
Includes bibliographical references and index.
Keywords: Deaf -- Congresses; Deaf -- Social conditions -- Congresses; Sign language -- Congresses